2006
DOI: 10.1086/504853
|View full text |Cite
|
Sign up to set email alerts
|

Predation Risk as a Driving Force for Sexual Segregation: A Cross‐Population Comparison

Abstract: Sexual segregation is widespread throughout the animal kingdom. Although a number of hypotheses have been proposed to account for observed patterns, the generality of the mechanisms remains debated. One possible reason for this is the focus on segregation patterns in large mammals such as ungulates, where the majority of studies are descriptions of a single population. Here, we present the results of a cross‐population comparison of patterns of sexual segregation in the Trinidadian guppy, Poecilia reticulata. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…To examine how predation risk differed as a function of water depth for our study population and to confirm the generality of previous findings (Croft et al 2006), we assessed predation risk to female guppies in shallow (23 cm) and deep (60 cm) areas in a sample of eight pools spanning the lower Turure River (including the pool where the study was carried out) using a standardized method (Croft et al 2006). In each pool, we lowered single female guppies (28-31 mm in length) confined in a clear, colourless plastic container tethered to a monofilament line at the two depths to observe predator behaviour towards this prey stimulus.…”
Section: K1mentioning
confidence: 70%
See 1 more Smart Citation
“…To examine how predation risk differed as a function of water depth for our study population and to confirm the generality of previous findings (Croft et al 2006), we assessed predation risk to female guppies in shallow (23 cm) and deep (60 cm) areas in a sample of eight pools spanning the lower Turure River (including the pool where the study was carried out) using a standardized method (Croft et al 2006). In each pool, we lowered single female guppies (28-31 mm in length) confined in a clear, colourless plastic container tethered to a monofilament line at the two depths to observe predator behaviour towards this prey stimulus.…”
Section: K1mentioning
confidence: 70%
“…This is emphasized in the Trinidadian guppy by the fact that we do not see sexual segregation in habitat use in river populations where large predators are absent in deeper waters (low-risk rivers; Croft et al 2006). Female ability to actively segregate from males will reduce levels of male contact and harassment.…”
Section: Discussionmentioning
confidence: 93%
“…Guppies in the Northern Range mountains of Trinidad live in geographically isolated rivers; in many of these rivers, dispersal of predators upstream is limited by waterfalls and rapids, so guppy populations in lowland reaches coexist and evolve under a substantial threat of predation, whereas in upland reaches, the risk of predation is substantially reduced ( 34 , 35 ). Trinidadian guppies have become a well-established model system for exploring the role of predation in the evolution of vertebrate behavior, life history, and morphology using a cross-population comparative approach ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this species, males spend the majority of their time in pursuit of females, employing both courtship and forced or coerced mating tactics (Magurran 2005). Previous research has documented high energetic costs of harassment to females, as indicated by decreased foraging opportunities (Magurran & Seghers 1994a), and females are known to employ a number of behaviours to reduce this harassment, including fleeing from harassing males (Magurran & Seghers 1994b) and occupying habitats that contain a low density of males such as areas of high predation risk (Croft et al 2006b;Darden & Croft 2008). Social familiarity is known to be important in structuring guppy social networks (Croft et al 2004(Croft et al , 2006a and they are capable of individual recognition (Ward et al 2009).…”
Section: Introductionmentioning
confidence: 99%